Study of caveolin-1 gene expression in whole adipose tissue and its subfractions and during differentiation of human adipocytes - Fernández-Real, José M (BioMed Central, 2010)
CONTEXT: Caveolins are 21-24 kDa integral membrane proteins that serve as scaffolds to recruit numerous signaling molecules. Specific subclasses of caveolae carry out specific functions in cell metabolism. In particular, triglycerides are synthesized at the site of fatty acid entry in one of these caveolae classes. OBJECTIVE AND METHODS: We studied the expression of caveolin-1 (CAV-1) gene in association with metabolic variables in 90 visceral and 55 subcutaneous adipose tissue samples from subjects with a wide range of fat mass, in the stromovascular fraction (SVC) and isolated adipocytes, and during differentiation of human adipocytes. RESULTS: CAV-1 gene expression was significantly decreased in visceral adipose tissue (v-CAV-1) of obese subjects. v-CAV-1 was positively associated with several lipogenic genes such as acetyl-coA carboxylase (ACACA, r = 0.34, p = 0.004) and spot-14 (r = 0.33, p = 0.004). In non-obese subjects v-CAV-1 also correlated with fatty acid synthase (FAS, r = 0.60, p < 0.0001). Subcutaneous (sc) adipose tissue (sc-CAV-1) gene expression was not associated with these lipogenic factors when obese and non-obese subjects were studied together. In obese subjects, however, sc-CAV-1 was associated with fatty acid synthase (FAS, r = 0.36, p = 0.02), sterol regulatory element binding protein-1c (SREBP-1c (r = 0.58, p < 0.0001), ACACA (r = 0.33, p = 0.03), spot-14 (r = 0.36, p = 0.02), PPAR-γ co-activator-1 (PGC-1, r = 0.88, n = 19). In these obese subjects, sc-CAV-1 was also associated with fasting triglycerides (r = -0.50, p < 0.0001). CAV-1 expression in mature adipocytes was significantly higher than in stromal vascular cells. CAV-1 gene expression in adipocytes from subcutaneous adipose tissue (but not in adipocytes from visceral adipose tissue) was significatively associated with fasting triglycerides. CAV-1 gene expression did not change significantly during differentiation of human preadipocytes from lean or obese subjects despite significant increase of FAS gene expression. CONCLUSION: Decreased CAV-1 gene expression was simultaneously linked to increased triglycerides and decreased lipogenic gene expression among obese subjects, paralleling the observations of hypertriglyceridemia in CAV-1 knockout mice. However, the regulation of CAV-1 gene expression seems independent of the adipogenic program.